The Importance of Carbohydrate Intake for Maintaining Glycogen Stores and Physical Performance during Prolonged Exercise : A Literature Review - Ismardi Ismardi; Dally Rahman; Muhamad Sazeli Rifki; Wilda Welis; Ardo Okilanda; Yovhandra Ockta (Jurnal Penelitian Pendidikan IPA, 2024)
The study investigates the critical role of carbohydrate intake in maintaining glycogen stores and enhancing physical performance during prolonged exercise. The primary aim is to evaluate how carbohydrate consumption influences glycogen levels and athletic performance, focusing on intake types and timing. Utilizing a qualitative descriptive research model, the study conducts an extensive literature review, involving a thorough search of scientific databases such as Scopus, ScienceDirect, and Google Scholar. Specific keywords like "Carbohydrates," "Glycogen Stores," and "Prolonged Exercise" guide the search for relevant articles. These articles are analyzed to extract and synthesize information on the relationship between carbohydrate intake and glycogen reserves during extended physical activities. The findings highlight that a daily carbohydrate intake of 6-12 g/kg body weight is essential for optimal glycogen levels and performance. Simple carbohydrates and fructose-glucose mixtures are particularly effective in enhancing recovery. Additionally, carbohydrate loading before intense exercise significantly improves glycogen stores and endurance performance. The study concludes that while adequate carbohydrate intake is vital for sustaining performance and facilitating recovery, further research is needed to explore the long-term effects and individual variations in carbohydrate nutrition strategies. This includes examining diverse exercise types, athlete profiles, and the interplay between carbohydrates and other dietary components